POPULIST RESSENTIMENT IN A MEDIATED CONTEXT - MARTIN, Claudiu (Studia Universitatis Babes-Bolyai Studia Europaea, 2024)
The aim of this article is to review the role that emotions play in populism, specifically ressentiment, and how it is strategically used on social media platforms to create polarization. Firstly, I define the two of the main characteristics that populism has had over time: the agonistic struggle between a people and an elite, and charismatic leadership. Secondly, I examine the significance of resentment as a political emotion and how it operates in extreme right-wing populism. Thirdly, I review how resentment has been applied in the context of social media and how these platforms offer the most effective means to generate social mobilization based on emotions through storytelling, which can anticipate the reactions of the public or users.